Asian Clam (Corbicula fluminea) Larvae Production in Broodstock Conditioning - Hadiana Hadiana; Aweng Eh Rak; Lee Seong Wei; M. Zharif (Department of Aquaculture, 2020)
Nowadays, the inclining of Asian clam market demand for supplying the seller Etak in some areas in Malaysia particularly Kelantan where etak had become the main concern due to the stock availability in the natural population was over-exploited. Thus, an effort to expedite the availability seed of Etak must be initiated to conserve the Asian clam population in their habitat. Until now, the information about production larvae is needed to begin the domestication process. The scientific goal aims to evaluate the best time to produce Asian clam larvae to supply the hatchery production process. To answer this question, the evaluation of broodstock conditioning adult Corbicula fluminea monthly during a year and this condition was compared into the fine sand sediment as well as no sediment. The results showed that the Asian clam adult pattern released larvae monthly during a year wherein the great number larvae were produced 22464 Ind/L totally in December and the produced larvae in Oct and Nov was almost similar with range 22350-22500 Ind/L. The condition index with fine sand sediment was 3.8419 % higher than the control treatment 3.5750 %. And last, the ingestion rate both treatment was 1.126 ± 0.534 μg/h and control treatment 1.609± 0.434 μg/h.